2009
DOI: 10.1093/rpd/ncp214
|View full text |Cite
|
Sign up to set email alerts
|

Radon monitoring in water sources of Balakot and Mansehra cities lying on a geological fault line

Abstract: This paper relates to a series of systematic studies regarding measurement of radon concentration in the earthquake-affected areas of northern Pakistan. Radon is a radioactive alpha-particle-emitting gas originating from the decay series of uranium and thorium and is found anywhere in soil, air and water. The nature of water does not matter with regard to the presence of radon, however, the level of radon concentration varies in different types of water. The present survey is carried out in water samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…The mean radon concentration of 9.4 ± 0.4 Bq l -1 in the water samples of this study is lower than the mean radon concentration of 15.52 ± 0.38 Bq l -1 in the water samples of Balakot and Mansehra area of Pakistan [30]. The elevated radon value in the water samples of the Balakot and Mansehra area of Pakistan is partly due to the fact that the region is situated on or in the vicinity of a major tectonically still active Bagh-Balakot Fault.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…The mean radon concentration of 9.4 ± 0.4 Bq l -1 in the water samples of this study is lower than the mean radon concentration of 15.52 ± 0.38 Bq l -1 in the water samples of Balakot and Mansehra area of Pakistan [30]. The elevated radon value in the water samples of the Balakot and Mansehra area of Pakistan is partly due to the fact that the region is situated on or in the vicinity of a major tectonically still active Bagh-Balakot Fault.…”
Section: Resultscontrasting
confidence: 74%
“…Our mean anural effective doses of 0.002 and 0.024 mSv a -1 due to ingestion and inhalation from radon in water are similar (within error limit) to the mean annual effective doses of 0.002 and 0.025 mSv a -1 of UNSCEAR due to ingestion and inhalation, respectively. In Table 3 radon concentrations and mean annual effective doses due to ingestion and inhalation from the drinking water sources of the study area have been compared with the results of similar studies conducted in the different regions and countries [29][30][31][32][33][34][35][36][37]. The mean radon concentration of 9.4 ± 0.4 Bq l -1 in the water samples of this study is higher than the mean radon concentration of 4.38 ± 0.44 Bq l -1 in drinking water samples of Murre area, Pakistan [29].…”
Section: Resultsmentioning
confidence: 99%
“…To protect the public from consequences of excessive exposure to radiation due to radon in their environment (Gillmore et al 2002), mainly from the risk of lung cancer, it is necessary to understand the levels of radon in each source including household water, particularly water from groundwater sources. A number of investigators have reported much higher radon concentrations in public drinking water around the world (Savidou et al 2001;Al-Kazwini and Hasan 2003;Xinwei 2006;Ali et al 2010;Khan et al 2010;Nikolov et al 2011;Bourai et al 2012;Muhammad et al 2012;Bourai et al 2012;Chandrashekara et al 2012). However, only few researchers have attempted to study the variation in dose exposure rate among different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a part of our previous work in which various building materials, environmental samples (soil, air, and water), food items and phosphatic fertilizers, and industrial wastes and by-products were analyzed for their naturally occurring radionuclides (Khan et al 1998(Khan et al , 2002(Khan et al , 2009a(Khan et al , b, 2010aKhan and Khan 2001;Jabbar et al 2003Jabbar et al , 2008Jabbar et al , 2009). In the present work, a comprehensive study of the soil, vegetation, vegetable, and water samples, collected from Northern areas of Pakistan, was carried out.…”
Section: Introductionmentioning
confidence: 99%